EFFORTS TO IMPROVE THE QUALITY OF HUMAN RESOURCES THROUGH THE PEKA PROGRAM (PRODUCTIVE, EDUCATIONAL, COOPERATIVE, AND ACTION) - Mulyadi Mulyadi; Muhammad Fadli Luran; Sudianto Sudianto; Andi Hidayatul Fadlilah (Yayasan Education and Social Center, 2022)
Human Resources are very significant. With technological advances in accelerating economic growth and the progress of a country, judging from the potential of these human resources, it is not surprising that the President of Indonesia, Mr. Jowowi, gave the name of his cabinet superior human resources in Advanced Indonesia. All programs implemented are always related to the progress and improvement of the Quality of Human Resources of the Indonesian people. The solution is to improve the Mindset of the people in Tj. Uma working as a day laborer peeling onions. Excellence hopefully can provide Motivation and Mindset Change in society so that PEKA